The Jonas’ Post Traumatic Stress Disorder in The Giver - Afni, Silfia (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This study aims analyze the main character’s stress disorder in Lois Lowry's novel, The Giver, using Gerald Davison's Theory of PostTraumatic Stress Disorder (PTSD). The research focuses on two objectives: (1) identifying the causes of PTSD experienced by Jonas in The Giver and (2) exploring the impacts of PTSD on Jonas in the novel. This research applied a literary criticism. This study used a literary psychology approach with Gerald Davison's post-traumatic stress disorder (PTSD) theory. The data source of this research was The Giver, a novel written by Lois Lowry, published in 1993 by Houghton Mifflin Company. It consists of 156 pages with 23 chapters. The findings of the study reveal that Jonas developed a mental disorder after undergoing compulsorytraining as the Receiver. His exposure to traumatic memories from The Giver instilled fear, pain, depression, and stress within him. The causes of his PTSD can be attributed to psychological, environmental, and brainstructure factors. Consequently, Jonas displayed negative and antisocial behaviors, frequently plagued by haunting thoughts related to his traumatic experiences. This led to significant changes in his behavior, emotions, and mindset.